Classroom management based on clap ice breaking to improve learning conduciveness - Fachrul Ananta Yasin (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2026)
This study aims to describe the implementation of classroom management based on clap ice breaking to enhance learning conduciveness in Grade 2 at MI NU Mathalibul Huda Mlonggo. The students tended to be active but had short attention spans and were easily distracted, which often caused the classroom to become noisy and less conducive to learning. This research applied a simple and fun ice breaking technique consisting of “Morning Clap” (1 clap), “Afternoon Clap” (2 claps), “Evening Clap” (3 claps), and “Night Clap” (accompanied by the “ssstttt” signal for complete silence). The results showed a significant improvement in classroom conduciveness, marked by reduced distractions, increased student attention, better classroom order, and a more enjoyable learning atmosphere. The clap ice breaking technique proved to be an effective, practical, and engaging strategy for classroom management. This study is expected to provide teachers with a simple yet powerful tool to create a conducive learning environment in elementary schools.